2021
DOI: 10.1590/s1679-49742021000400006
|View full text |Cite
|
Sign up to set email alerts
|

Tendência dos casos de sífilis gestacional e congênita em Minas Gerais, 2009-2019: um estudo ecológico

Abstract: Resumo Objetivo: Analisar a tendência das notificações de sífilis gestacional e congênita em Minas Gerais, Brasil, de 2009 a 2019. Métodos: Estudo ecológico de série temporal, considerando-se como unidade de análise o estado de Minas Gerais, a partir de dados notificados no Sistema de Informação de Agravos de Notificação (Sinan). Empregou-se o modelo autorregressivo de Prais-Winsten para verificação de tendência. Resultados: Foram notificados 20.348 casos de sífilis gestacional e 11.173 casos de sífilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
0
9
0
15
Order By: Relevance
“…Esta realidade corrobora com a que foi identificada em outros estudos realizados em São Paulo, Minas Gerais, Mato Grosso do Sul e Tocantins 24,[28][29][30] . A respeito da variável raça/cor, este estudo aquiesceu o resultado em estudo realizado em 2019, pois o trabalho concluiu frequência mulheres brancas em 66% dos casos 24 .…”
Section: Resultsunclassified
“…Esta realidade corrobora com a que foi identificada em outros estudos realizados em São Paulo, Minas Gerais, Mato Grosso do Sul e Tocantins 24,[28][29][30] . A respeito da variável raça/cor, este estudo aquiesceu o resultado em estudo realizado em 2019, pois o trabalho concluiu frequência mulheres brancas em 66% dos casos 24 .…”
Section: Resultsunclassified
“…In Minas Gerais, from 2009 to 2019, the incidence rates of gestational and CS had an average percentual annual increase of 36.7% and 32.8%, respectively, suggesting failure on the syphilis treatment during the prenatal 21. In Amazonas, Ceará, Federal District, Espírito Santo, Rio de Janeiro and Rio Grande do Sul, 43% of women who received a diagnosis of gestational syphilis progressed to CS, 59% of them received inadequate treatment, 25% were untreated and only 7.9% of partners were treated 22.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding CS vertical transmission should be provided to pregnant women at the onset of prenatal care, and physicians must inform patients regarding the risks and consequences of the disease to the mother and her fetus [ 32 , 42 ]. Nonetheless, difficulties in diagnosis, interruption of and/or low attendance in prenatal examinations, non-adherence or inadequate treatment regarding antibiotic dosage, and absence of partners at prenatal appointments have been reported as risk factors for the development and non-interruption of syphilis [ 42 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified spatial clusters of municipalities with high rates of CS and SiP in Brazil. Between 2001 and 2017, almost all regions and microregions of the country reported a higher intensity of CS and SiP infections [ 47 , 54 , 57 – 62 ]. However, in most of Brazil’s microregions, there are few studies of these regions that do not highlight these areas as priority for a syphilis surveillance study.…”
Section: Discussionmentioning
confidence: 99%